2015
DOI: 10.1128/jvi.01856-14
|View full text |Cite
|
Sign up to set email alerts
|

Eilat Virus Host Range Restriction Is Present at Multiple Levels of the Virus Life Cycle

Abstract: Most alphaviruses are mosquito-borne and exhibit a broad host range, infecting many different vertebrates, including birds, rodents, equids, humans, and nonhuman primates. This ability of most alphaviruses to infect arthropods and vertebrates is essential for their maintenance in nature. Recently, a new alphavirus, Eilat virus (EILV), was described, and in contrast to all other mosquito-borne viruses, it is unable to replicate in vertebrate cell lines. Investigations into the nature of its host range restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 64 publications
2
87
0
Order By: Relevance
“…However, how ISFs are hindered from infecting vertebrate cells is of special interest in studying virus emergence. The only reverse genetics-based data available in this field have been generated recently from EILV, a novel alphavirus related to the WEEV serocomplex of arbo-alphaviruses, where restriction occurs at the levels of both entry and replication (14, 15). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, how ISFs are hindered from infecting vertebrate cells is of special interest in studying virus emergence. The only reverse genetics-based data available in this field have been generated recently from EILV, a novel alphavirus related to the WEEV serocomplex of arbo-alphaviruses, where restriction occurs at the levels of both entry and replication (14, 15). …”
Section: Discussionmentioning
confidence: 99%
“…EILV is in a sister relationship with vertebrate-infecting alphaviruses of the Western equine encephalitis virus (WEEV) complex (14). Studies of the replication of an EILV replicon, as well as chimerized constructs in which EILV protein domains were replaced by homologous domains of the arbo-alphavirus Sindbis virus (SINV), revealed that EILV is blocked at two independent stages of the replication cycle, namely, RNA replication and viral entry (14, 15). The latter findings were further supported by in vivo infection experiments in mosquitoes and newborn mice.…”
Section: Introductionmentioning
confidence: 99%
“…As briefly discussed earlier, the Eilat alphavirus is an ISV found to be host restricted at multiple levels (Nasar et al, 2012(Nasar et al, , 2015b. This profound degree of host restriction coupled to the phylogenetic clustering to the WEE complex of alphaviruses, has allowed for the synthesis of Eilat/chikungunya chimeras for use as ELISA antigens with native structure and conformation and without the need for inactivation .…”
Section: Vaccine and Diagnostic Applications Of Isvsmentioning
confidence: 99%
“…Standard plaque assays were performed for the samples positive by qRT-PCR with Vero cells. Anti-CHIKV IgM-capture enzyme-linked immunosorbent assays (ELISAs) ( 8 ) were performed by using a chimeric Eilat-CHIKV ( 9 ) that contained the nonstructural proteins from Eilat virus and structural proteins from CHIKV, resulting in a structure indistinguishable from that of CHIKV. Plaque-reduction neutralization tests were used to confirm ELISA results.…”
Section: The Studymentioning
confidence: 99%